POLA KOMUNIKASI ORANG TUA DALAM KELUARGA ANAK PUTUS SEKOLAH DI DESA LADANG LAWEH KABUPATEN AGAM SUMATERA BARAT - Rahmat Novialdi; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Drop out occurs in children of childbearing age who on average are boys. Out-of-school children come from families who are able to finance higher education. The busyness of parents about work, makes the lack of effective communication between parents and children, and the low role of parents in providing support and motivation to pay attention to children's education so that children seek their own activities to forget their obligations. This study aims to determine the pattern of communication of parents in families of out of school children in the village of Ladang Laweh and the factors that influence the pattern of communication of parents in families of out of school children in the village of Ladang Laweh. This study uses a qualitative method with a descriptive approach and by taking informants using Snowball techniques data collection techniques of observation, interviews and documentation. Whereas for the technique of checking the validity of the data, the researcher used data triangulation and extended participation. The data obtained is then processed to be reduced, presented to produce a general conclusion. The results of this study indicate that the pattern of parental communication in families of out of school children in the village of Ladang Laweh is permassive (free) communication that there is more trust from parents to children to do something, parents have the attitude to yield to children, no punishment given by parents if the child violates and there are no rules set for the child. An authoritarian pattern of communication where there is a firm attitude, restraint, anger, and a punishment for those who violate. Factors that influence the pattern of parental communication in families of out of school children in the village of Ladang Laweh have a factor inability to express the need to educate children in education, some say it is not an obligation to complete education and some say that inability to cause children drop out and decision factors on themselves own lack of attention is caused by parents and the absence of effective communication of parents with children